Trade-Induced Adoption of New Work - Gueyon Kim (Institute of Labor Economics (IZA), 2022)
I study the trade-induced restructuring process using a novel measure of new work that captures the firm's demand for jobs employing new knowledge, skills, and technologies. To construct measures of new work, I identify newly emerged job titles using word embedding models. Using both regional and firm-level analyses, I find that greater import exposure causes a persistent increase in new work in managerial occupations, but a decrease in new work in other occupations. Examining the activities performed in managerial new work, I find evidence of increased investments in post-production activities such as customer support, marketing, and sales. I further show that the trade-induced increase in managerial new work is driven by college-educated workers, thereby shedding light on the role of new work adoption in the distributional consequences of import shocks.
Keywords: F16; J23; O33; R12; 330; new work; trade adjustments; labor market inequality